Gleditsia saxatilis (Fabaceae), a new species from limestone areas of Guangxi, China based on morphological and molecular evidence - Lu, Zhao-Cen; Huang, Zhang-Ping; Yang, Ping; Huang, Yu-Song; Liu, Yan (Phytotaxa, 2021)
Gleditsia saxatilis Z.C.Lu, Y.S.Huang & Yan Liu, a new species was found from limestone areas of Guangxi, China. The morphological and phylogenetic analyses showed that G. saxatilis is similar to G. sinensis, but differs by its habit indeciduous, winter buds globose or subglobose, apex round, petiolules glabrescent to glabrous, leaflets 2–4 pairs, leathery, both sides glabrous, racemes shorter, 2.5–7 cm long, ovary glabrous, legume slightly falcate, stipe 3–8 mm long.